2016
DOI: 10.1016/j.jaci.2015.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations and outpatient visits for rhinovirus-associated acute respiratory illness in adults

Abstract: Background Rhinovirus is linked to asthma exacerbations and chronic obstructive pulmonary disease exacerbations in adults. The severity and rates of rhinovirus acute respiratory illnesses (ARI) in adults are uncertain. Objectives We determined rhinovirus-associated ARI rates in adults presenting for care in multiple settings and identified factors associated with rhinovirus detection. Methods This prospective, population-based cohort enrolled Tennessee residents ≥18 years old in the emergency department (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 72 publications
1
16
1
3
Order By: Relevance
“…However, a slightly larger proportion of the asthmatic subjects were examined outside the common cold season, which may have reduced the chance of finding HRV in asthmatics relative to controls. Furthermore, the difference in HRV prevalence between the groups was seen in spite of the fact that a significantly larger proportion of control subjects than asthmatics were smokers, a factor that may increase susceptibility to HRV infections [23,24]. Accordingly, there was a trend towards higher prevalence of smokers in HRV þ asthmatics versus HRV À asthmatics in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…However, a slightly larger proportion of the asthmatic subjects were examined outside the common cold season, which may have reduced the chance of finding HRV in asthmatics relative to controls. Furthermore, the difference in HRV prevalence between the groups was seen in spite of the fact that a significantly larger proportion of control subjects than asthmatics were smokers, a factor that may increase susceptibility to HRV infections [23,24]. Accordingly, there was a trend towards higher prevalence of smokers in HRV þ asthmatics versus HRV À asthmatics in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…RV infection can induce lower respiratory tract symptoms, including cough, shortness of breath, chest tightness, and wheezing in patients with underlying asthma or other chronic lung diseases [13•, 3438]. As IgE levels rise, the severity of lower respiratory tract symptoms increases in the asthmatic group [30].…”
Section: Rhinovirus-induced Respiratory Pathogenesismentioning
confidence: 99%
“…Rhinovirus (RV) accounts for 60–70 % of these virus-associated exacerbations in children over the age of 3 [512]. And, while a less frequent an occurrence, RV infections remain a common cause of asthma exacerbations throughout adulthood [13•]. In our studies at the University of Virginia, RV infections were identified in 61 % of children aged 3–18 years hospitalized with an asthma exacerbation [14] with similar numbers observed in a follow-up study that was performed in Costa Rica [15].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Respiratory viruses are one of the most common causes of asthma exacerbations in both adults and children. [3][4][5][6] Furthermore, increasing evidence is emerging to suggest that viral respiratory infections in early life are related with the medium and long-term development of asthma. 7,8 This article aims first to review the role of viruses as precipitating factors for asthma, and then to summarize the current state of knowledge on their role in asthma exacerbations.…”
Section: Introductionmentioning
confidence: 99%